2017
DOI: 10.1016/j.pneurobio.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Where are we? The anatomy of the murine cortical meninges revisited for intravital imaging, immunology, and clearance of waste from the brain

Abstract: Rapid progress is being made in understanding the roles of the cerebral meninges in the maintenance of normal brain function, in immune surveillance, and as a site of disease. Most basic research on the meninges and the neural brain is now done on mice, major attractions being the availability of reporter mice with fluorescent cells, and of a huge range of antibodies useful for immunocytochemistry and the characterization of isolated cells. In addition, two-photon microscopy through the unperforated calvaria a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
134
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(138 citation statements)
references
References 557 publications
(1,002 reference statements)
1
134
1
2
Order By: Relevance
“…Neuromodulators from meningeal lymphatics can even possibly modulate brain tissue by their direct release into CSF 6 . A recent animal study was, however, unable to reproduce passage of CSF tracer into dural lymphatic vessels 7 and was thus in line with previous observations indicating that the arachnoid constitutes an impermeable barrier layer between the CSF and dura mater 8,9 .…”
supporting
confidence: 77%
“…Neuromodulators from meningeal lymphatics can even possibly modulate brain tissue by their direct release into CSF 6 . A recent animal study was, however, unable to reproduce passage of CSF tracer into dural lymphatic vessels 7 and was thus in line with previous observations indicating that the arachnoid constitutes an impermeable barrier layer between the CSF and dura mater 8,9 .…”
supporting
confidence: 77%
“…To date, very few studies have investigated the role of dural myeloid cells in neuroinflammation. This lack of consideration may be partially due to the fact that the dura is the outermost layer of the meninges with its own noncerebral blood supply and thus is not in direct contact with the CNS parenchyma and is separated from the CSF by the arachnoid barrier (Coles, Myburgh, Brewer, & McMenamin, ). However, it was recently shown that dural lymphatic vessels absorbed CSF and brain interstitial fluid (via the “glymphatic” pathway) and drained into the deep cervical lymph nodes (Aspelund et al, ; Louveau et al, ; Louveau, Smirnov, et al, ), suggesting that the dura may represent an immunological interface between the CNS and the periphery.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, the relationship between the classic concept of the venous lacunae and the meningeal lymphatics has not been fully elucidated. 9 It was reported that the cross-sectional dimension of the visualized lymphatic vessels was difficult to measure but was approximately 0.5 mm, similar in size to the resolution of high-resolution imaging sequences. This estimate is in line with that observed by MRI and histology in the previous work by Absinta et al 5 The meningeal lymphatics are the drainage route of waste and CSF from the brain.…”
Section: Magnetic Resonance In Medical Sciencesmentioning
confidence: 95%